Gouty tophi of small joints of hand: A classical presentation - Kumari, Manju; Singh, Mukul (Indian Journal of Case Reports, 2019)
Gout is an acute inflammatory disorder caused by deposition of monosodium urate crystals. Gouty tophus can be the initial presenting feature of chronic disease. Diagnosis of periarticular nodules can be a challenge for clinicians. Fine needle aspiration can provide quick, cost-effective and definitive diagnosis for the early management of these patients. Here, we present the case of gouty tophi of the right-hand index finger in a 45-years-old male leading to restricted finger movements.